Pengaruh Media E-Comic Terhadap Keterampilan Menulis Teks Prosedur Peserta Didik Sekolah Dasar - Mei Sulistyowati; Ermawati Zulikhatin Nuroh (JPDI (Jurnal Pendidikan Dasar Indonesia), 2026)
This study aims to determine the effect of using e-comic media on elementary school students’ skills in writing procedural texts. The background of this research is the students’ low ability in writing procedural texts and the limited variety of innovative media used by teachers. The study employed a quantitative method with a pre-experimental design, specifically the one-group pretest-posttest model. The sample consisted of 30 fourth-grade students from SDN Gamping 1. Data were collected through written tests and classroom observation, with writing performance evaluated based on content relevance, grammar, structure, spelling, and sentence formation. The data were analyzed using descriptive statistics and paired samples t-test with SPSS. The results revealed a significant improvement in students’ writing skills. The average score increased from 57.92 in the pretest to 76.46 in the posttest, with a statistically significant difference (p < 0.05), indicating the effectiveness of e-comic media in enhancing students’ procedural text writing abilities. In conclusion, e-comic media fostered students’ motivation and understanding through visual storytelling and contextual learning. These findings suggest that e-comics can serve as an engaging and effective alternative to traditional instructional methods in elementary writing education.